The development of mental scenario building and episodic foresight. (15th July 2013) - Suddendorf, Thomas; Redshaw, Jonathan
Abstract : Episodic foresight is the future‐directed counterpart of episodic memory. It is a sophisticated, potentially uniquely human capacity, with tremendous adaptive consequences. Here we review what is currently known about its development through early childhood. We tackle this from two distinct perspectives. First, we present the first systematic evaluation of the development of purported components of mental scenario building as highlighted by a theater metaphor: the stage, the playwright, the set, the actors, the director, the executive producer, and the broadcaster. We find that, although there are diverse developmental trajectories, by 4 years of age children have acquired the basic cognitive components required to mentally construct specific future events. Second, we examine recent attempts to test children's episodic foresight more directly and find that results are in line with those examining the development of required components. This is not to say that children younger than four have no inkling of upcoming events or that older children have nothing left to learn about constructing the future. Episodic foresight, and its neurocognitive foundations, continues to develop throughout childhood.